Conformation of DNA in chromatin protein-DNA complexes studied by infrared spectroscopy. - Liquier, J (1979)
The following observations concerning the DNA secondary structures in various nucleohistone complexes were made by infrared spectroscopy: 1/ in chromatin, chromatin extracted by 0.6 M NaCl, nucleosomes, and histone-DNA reconstituted complexes, the DNA remains in a B type conformation at low relative hygrometry; 2/ in chromatin extracted by tRNA and in non histone protein-DNA reconstituted complexes, the DNA can adopt an A type conformation. Infrared linear dichroism data show that in NHP-DNA complexes the low relative hygrometry conformation of DNA may be modified and that the infrared parameter -1090 is close to that measured for RNA's or DNA-RNA hybrids. It is concluded that the histones block the DNA in a B form and that some of the NHP could be involved in the control of the secondary structure of DNA in chromatin.